Hematology and plasma biochemistry reference intervals for free-living adult chimango caracara (Milvago chimango) during the nonbreeding season - Paterlini, Carla Ángela (2023)
Hematological and blood biochemistry values are useful in assessing the physiological, nutritional, and overall health status of captive and free-living wildlife. For the chimango caracara (Milvago chimango), the most common raptor species in Argentina, reference intervals (RIs) for hematology and blood biochemistry are lacking. For this study, 86 chimango caracaras were captured and studied in Mar del Plata and neighboring areas (Buenos Aires, Argentina) during winter (April–July) in 2018 and 2019. This is the first study to present RIs for 33 blood parameters in a large number of free-living chimango caracaras during the nonbreeding season. In addition, the variability of blood parameters according to sex and calendar year was analyzed. Overall, values for the studied parameters were similar to those described for other raptor species. There were significant differences between years for absolute monocyte counts, relative eosinophils, monocyte counts, glucose, phosphorus, and alanine aminotransferase. Only the relative count of eosinophils, aspartate aminotransferase, and calcium showed significant differences between the sexes. The values of absolute monocyte counts and the relative count of eosinophils and monocytes, glucose, phosphorus, and alanine aminotransferase were higher in 2019 than in 2018, whereas mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration were higher in 2018. Relative eosinophil counts were higher for males than for females, and aspartate aminotransferase activity and calcium concentration were significantly higher for females than for males. The RIs for hematology and plasma biochemistry from this large number of chimango caracaras is of clinical relevance not only for chimango caracaras under medical care in rehabilitation centers but also in ecological studies aimed to investigate the physiological responses of this species to natural and anthropogenic changes.